Prebiotik inulin - Mičović, Elizabeta (Zdravstveno varstvo, 2006)
Functional foods and food products maintain and improve health and prevent many illnesses. Functional foods have been recently defined as foods providing physiological health benefits based on scientific evidence. Dietary fibre exerts beneficial effects on digestion and absorption, as well as on bowel mucosa and metabolism, and is therefore regarded as one of basic food constituents. Beneficial physiological effect on health are also provided bysoluble dietary fibre and prebiotic inulin. Incorporating inulin into diet is the perfect way to increase the faecal bulk and stool frequency, as well asto lower the intestinal pH, shorten the faecal transit time and improve the absorption of minerals. The paper presents the results of studies dealingwith the effects of inulin on symptoms of different diseases, such as constipation, diabetes type II, colorectal disease, osteoporosis and obesity. Properties of inulin, use of inulin in food industry and possible future usesof this prebiotic are discussed.
Keywords: food; funkcionalna živila; inulin; prebiotiki; prehrana; vlaknine